Methyl‐Selective α‐Oxygenation of Tertiary Amines to Formamides by Employing Copper/Moderately Hindered Nitroxyl Radical (DMN‐AZADO or 1‐Me‐AZADO) - Nakai, Satoru; Yatabe, Takafumi; Suzuki, Kosuke; Sasano, Yusuke; Iwabuchi, Yoshiharu; Hasegawa, Jun‐ya; Mizuno, Noritaka; Yamaguchi, Kazuya (Angewandte Chemie International Edition, 2019)
Methyl‐selective α‐oxygenation of tertiary amines is a highly attractive approach for synthesizing formamides while preserving the amine substrate skeletons. Therefore, the development of efficient catalysts that can advance regioselective α‐oxygenation at the N‐methyl positions using molecular oxygen (O2) as the terminal oxidant is an important subject. In this study, we successfully developed a highly regioselective and efficient aerobic methyl‐selective α‐oxygenation of tertiary amines by employing a Cu/nitroxyl radical catalyst system. The use of moderately hindered nitroxyl radicals, such as 1,5‐dimethyl‐9‐azanoradamantane N‐oxyl (DMN‐AZADO) and 1‐methyl‐2‐azaadamanane N‐oxyl (1‐Me‐AZADO), was very important to promote the oxygenation effectively mainly because these N‐oxyls have longer life‐times than less hindered N‐oxyls. Various types of tertiary N‐methylamines were selectively converted to the corresponding formamides. A plausible reaction mechanism is also discussed on the basis of experimental evidence, together with DFT calculations. The high regioselectivity of this catalyst system stems from steric restriction of the amine‐N‐oxyl interactions. Mild and selective: The methyl‐selective α‐oxygenation of various tertiary amines to the corresponding formamides (30 examples) is achieved by employing copper and a moderately hindered nitroxyl radical (DMN‐AZADO or 1‐Me‐AZADO) under mild conditions. The high regioselectivity of this catalyst system stems from steric restriction of the amine–N‐oxyl interactions.